Educative Effects of Bolsa Familia: Brazil in Latin American Context - Crosta, Facundo (2017)
This paper analyzes the relationship between educational outcomes in access and socioeconomic levels of the population from Brazil, focusing on conditional cash transfer (CCT) programs (Bolsa Escola/Bolsa Familia) and the comparison between Brazil and the rest of Latin America in terms of improvements in educational outcomes. To do this, we analyze, for the 2000–2014 period, different indicators of educational outcomes at the aggregate level and/or income levels and poverty. These analyses are realized on the basis of microdata by country and year, homogeneously processed according to the criteria of the SEDLAC base. We conclude that the positive effect of that program is a robust conclusion, both in terms of impact studies and the evolution of aggregate data. It is also observed that Brazil must intensify efforts in basic education so as not to be left behind in the context of Latin America. Finally, the lack of progress in the tertiary/university sector calls for some thought on whether it is not necessary to modify the conditionalities of the program.